The Persian Pickle Club - Dallas, Sandra (New York : St. Martin's Press, 1995)
Loyalty and friendship within The Persian Pickle Club, a Depression-era farm town women's quilting and gossip club, is put to the test when a city girl joins.
Wilson's Fiction.
Adult
Keywords: City and town life -- Kansas -- Fiction; Depressions -- Kansas -- Fiction; Women -- Kansas -- Societies and clubs -- Fiction; City and town life -- Fiction; Depressions -- Fiction; Historical fiction; Women -- Societies -- Fiction; Kansas -- Fiction; Kansas -- Fiction; Historical fiction